ANALISIS IMPLEMENTASI KEBIJAKAN PENDIDIKAN PADA SEKOLAH PINGGIRAN: STUDI KASUS DI SMPN 51 MERANGIN - Hanibar; Hasmailena Saragih; Sisca Yuliasary; Evi Susanti; Desi Khoridatul (STKIP Subang, 2026)
This study aims to analyze the implementation of education policies at SMPN 51 Merangin, specifically the implementation of the Independent Curriculum, literacy and numeracy achievements, and the utilization of school infrastructure. The background of the study stems from low national learning outcomes and disparities in education quality between regions (OECD, 2023; Ministry of Education and Culture, 2023; World Bank, 2022). The study used a qualitative approach with a case study design through interviews, observations, and analysis of school documents. The results show that the implementation of the Independent Curriculum is not optimal due to variations in teachers' understanding of differentiated learning and authentic assessment. Student literacy and numeracy achievements remain low, at 35% and 43%, respectively. Infrastructure such as digital devices, internet access, and project learning facilities are also limited. These findings confirm that teacher competence, school resource readiness, and the learning environment play a critical role in the success of policy implementation. The study recommends improving teachers' pedagogical competence, strengthening learning support facilities, and implementing literacy and numeracy program interventions to improve the quality of education in remote schools.Keywords: keyword 1, keyword 2, keyword 3